State or private security supply? An analysis from the institutional economics perspective - Wolfgang Bretschneider; Andreas Freytag; Johannes Rieckmann; Tim Stuchtey (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2022)
The issue of internal security has become increasingly complex over the past decades. As there is an increasing overlap between private and public provision of security, the question of how to allocate responsibility for security between the public sphere (state) and the private sphere has become important. The literature suggests that this question cannot be answered based on a simple private vs. public binarity. Concepts that can provide both clarity and sufficient complexity are much needed. This article offers an institutional economics concept based on the difference between provision and production, and discusses selection criteria for public vs. private provision, and production of protection services at three different stages: punishment as deterrence; patrol services; and self-defence. What stands out is that a unique characteristic of the economic good 'protection service' is of particular relevance for the level of provision as well as of production: the potential repressivity.
Keywords: H41; H42; K42; L33; L51; 330; protection; privatisation of security; homeland security; civil security; economicsof security; public good; publicly provided good; security industry